Prenatal diagnosis of chromosome abnormalities Noninvasive prenatal testing - Quiroga de Michelena, María Isabel (2016)
Non-invasive prenatal test (NIPT) is a screening method that identifies pregnant women with a high aneuploidy risk, specifically for trisomy 21, 18, 13, and chromosome X anomalies. NIPT analyzes free fetal DNA found in maternal blood. In this review, we describe the benefits, disadvantages and study indications.